Evaluating delays in non-compounded prescription services under health coverage - Fatimah, Ratnah; Nurfikri, Ari (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Hospital pharmaceutical services are critical to achieving high-quality healthcare. Waiting time for outpatient prescription services is a key performance indicator and a major concern for patients, particularly in Indonesia’s BPJS Kesehatan (National Health Insurance) program. At Hermina Bekasi Hospital, long prescription wait times have led to patient dissatisfaction, prompting this study to evaluate the waiting time for non-compounded prescriptions to assess compliance with national standards. Methods: This study employed a mixed methods design with an explanatory sequential approach. The quantitative phase involved observing 100 non-compounded outpatient prescriptions in March 2023 to measure waiting times. Data were analyzed for average durations and compliance with the ≤30-minute standard set by the Ministry of Health. The qualitative phase included in-depth interviews with five pharmacy staff, using an input-process-output framework to identify underlying causes of delay. Findings: Only 2% of prescriptions met the 30-minute standard; the average waiting time was 1 hour and 50 minutes, with a maximum of 3 hours and 32 minutes. The verification stage was the most time-consuming. Factors contributing to delays included inadequate human resources, insufficient facilities and infrastructure, SOP implementation gaps, overlapping doctor practice hours, and distant medication storage. These delays caused patient complaints and risked non-compliance with hospital accreditation benchmarks. Conclusion: The waiting time for non-compounded outpatient prescription services at Hermina Bekasi Hospital fails to meet national standards. Improvements are urgently needed in human resources allocation, doctor scheduling, infrastructure, and process efficiency to reduce delays and enhance service quality. Novelty/Originality of this article: This study offers a comprehensive evaluation using a mixed-methods framework to diagnose systemic inefficiencies in prescription services within a BPJS healthcare setting. The integration of both quantitative and qualitative insights provides actionable recommendations, such as layout redesign and warehousing solutions, which are often overlooked in similar studies.